A boy once lived in Nazareth - Taylor, Florence Marian (Tompkins) 1892-; Ebert, Len. (New York H. Z. Walck, 1969)
Life and customs in Biblical Nazareth are presented in a description of the childhood of Jesus.
Portions of this book appeared previosuly in In Wisdom and in stature, c1942 by Whitmore and Stone.
Keywords: Jesus Christ -- Childhood; Jesus Christ -- Childhood